La motricidad gruesa y el desarrollo del esquema corporal de los niños de 4 a 5 años del Centro del Educación Inicial “Amiguitos” - Mancheno Sagñay, Paola Esthefania (2024)
The research work entitled "Gross Motor Skills in the Development of Body Schema in Children Ages 4 to 5 at the Amiguitos Early Childhood Education Center, City of Riobamba" seeks to solve the specific difficulties with gross motor skills in the development of body schema presented in children of this level. These difficulties include [specific challenges], which were identified through a primary and field study using a quantitative and qualitative approach and a non-experimental design. This led to working with ten children from Initial II, using observation as a technique and an observation sheet as an instrument containing ten items. The data obtained from applying the instrument allowed data to be collected, tabulated, graphed, analyzed, and interpreted, which allowed us to reveal that there is difficulty in managing gross motor skills and body schema. For this, playful strategies were created to improve gross motor skills in developing body schema, including five activities that can be applied inside and outside the classroom. Teachers will be able to promote the comprehensive development of infants in areas related to gross motor skills and body schema.